Research and Application of Development Model of Information Service for IOT of Oil and Gas Production Based on Cloud Architecture - Wu Haili; Gong Renbin; Wang Congbin; Gong Lei (Universitas Ahmad Dahlan, 2017)
On completion of oil and gas production IOT system application system needs expanding and secondary problems such as software development integration service, this paper proposes a scalable cloud platform(called A11-PaaS) based on middleware and ESB(Enterprise service bus). The platform realizes that managmant of ESB, controls the service request access on the ESB with the LDAP, use the WAS profile as a sandbox for the development, combine with the Maven plug-in and Nexus, realize the unified management of the secondary development, testing, and deployment of the new system and achieve the purpose of rapid development. The platform has been deployed in some oil company, the experimental results show that this technology has achieved rapid development, integrated the web service from IOT system, and provide effective method to integrate other application system.